Unleashing the competitive advantage of Malaysian private housing developers through product analysis - Mastura Jaafar,; Azlan Raofuddin Hj Nuruddin,; Syed Putra Syed Abu Bakar,; Faraziera Mohd Raslim, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Malaysian housing developers produce a range of products that has the characteristics of being large, expensive and durable. Nonetheless, the protracted development process exposes the developer to a high level of risk. Previous product development studies had focused on the technical elements of development rather than managerial aspects. This paper examines the contribution of product characteristics to the competitive advantage of Malaysian private housing developers. Using semi-structured snowball interviews, this qualitative study aims to elucidate upon the success factors of private housing developers. Ten successful housing developers were chosen for this research. The findings suggest that successful project management coupled with a product selling price that reflects the location, quality and innovativeness of the product, count toward the developer’s reputation and branding. This paper expands the academic housing development literature by providing specific and indepth information on housing developer products in Malaysia.